Analisis Dan Benchmarking Disk Performance Pada Windows Azure Virtual Machine (vm) Dan Amazon Web Service Ec2 - Syihan Qaes Yamani; Rd Rohmat Saedudin; Ahmad Almaarif (eProceedings of Engineering, 2020)
Abstrak Pada era teknologi ini peran dari cloud computing sangat membantu penggunanya baik manusia secara individu maupun perusahaan. Cloud Computing sendiri adalah suatu layanan teknologi informasi dimana resource diambil dari internet melalui tool dan aplikasi berbasis website dan tidak terkoneksi lansung ke server. Terdapat dua contoh layanan cloud computing yaitu Windows Azure, dan Amazon Web Services. Pada analisis ini membahas perbandingan kinerja dan layanan disk performance dari dua platform Cloud Computing yaitu Amazon Web Services dan Microsoft Azure. Platform diuji menggunakan Virtual Machine yang sudah di sediakan dari masing-masing platform. Pengukuran performa dilakukan dengan menggunakan Phoronix Test Suite pada size b1ms, b2s, dan b2ms pada Windows Azure dan t2.small, t2.medium, dan t2 large pada Amazon Web Services dan hasil yang disajikan berupa parameter IOzone Write, IOzone Read, Dbench, dan UnpackKernel. Kata Kunci: Windows Azure, Amazon Web Services, disk performance Abstract In this technological era the role of cloud computing is very helpful for users both individuals and corporate individuals. Cloud Computing itself is an information technology service where resources are taken from the internet through web-based tools and applications and not connected to direct servers. There are three examples of cloud computing services namely Windows Azure, and Amazon Web Services. This analysis discusses the application of disk performance and service performance from the Cloud Computing platform, namely Amazon Web Services and Microsoft Azure. Platforms value using Instances that have been provided from each platform. Performance measurements are carried out using the Phoronix Test Suite at b1ms, b2s, and b2ms in Windows Azure and t2.small, t2.medium, and large t2 at Amazon Web Services and the results contain the parameters IOzone Write, IOzone Read, Dbench, and Unpack-Kernel. Keywords: Windows Azure, Amazon Web Services, disk performance